Physicochemical modification of gliadin by black tea polyphenols: insight towards a nutraceutical therapy for celiac disease - Mathews, Paul, author; Van Buiten, Charlene, advisor; Gentile, Chris, committee member; Chung, Jean, committee member (Colorado State University. Libraries, 2022)
Celiac disease is an autoimmune disorder that affects approximately 1% of the global population. The pathogenesis of celiac disease is complex, involving the innate and adaptive immune responses. Exposure to gluten amongst genetically susceptible individuals initiates and propagates the disease process, with autoimmunity against endogenous tissue-transglutaminase enzymes manifesting intra- and extra-intestinal symptoms. Currently, the only mitigation strategy for celiac disease is an adherence to a gluten-free diet, which can be difficult to maintain. Recent advances in synthetic and natural products chemistry may offer therapeutic alternatives to the total abstinence from gluten containing products. The overarching objective of our research is to develop a nutraceutical approach to treating celiac disease using dietary polyphenols from tea. Within this thesis, we used a multi-spectroscopic approach to show that black tea polyphenols, which are rich in theaflavins and other flavanols, interact with gluten proteins in vitro to form colloidal complexes that result in structural change to the protein. These changes have the potential to reduce the immunogenicity of gluten via interference with digestion, sequestration, and conformational changes which may reduce recognition of the protein by immune cells. The interactions investigated here offer promise as a nutraceutical, plant-based therapy to acute gluten exposure in susceptible individuals.
Keywords: celiac disease; multispectroscopic; polyphenols; gliadin; black tea; nutraceutical